Using the latency correction method to calculate the tonic stretch reflex threshold in spastic cerebral palsy pre and post exercise intervention: a case study - Frick, Justin (2024)
ABSTRACT Frick, J. 2024. Using the latency correction method to calculate the tonic stretch reflex threshold in spastic cerebral palsy pre and post exercise intervention: a case study, Faculty of Sport and Health Sciences, University of Jyväskylä, Master’s thesis, 75 pp. 0 appendices.